Innovation in detection of microparticles and exosomes - Pol, E.; Coumans, F.; Varga, Z.; Krumrey, M.; Nieuwland, R. (Journal of thrombosis and haemostasis, 2013)
Summary Cell‐derived or extracellular vesicles, including microparticles and exosomes, are abundantly present in body fluids such as blood. Although such vesicles have gained strong clinical and scientific interest, their detection is difficult because many vesicles are extremely small with a diameter of less than 100 nm, and, moreover, these vesicles have a low refractive index and are heterogeneous in both size and composition. In this review, we focus on the relatively high throughput detection of vesicles in suspension by flow cytometry, resistive pulse sensing, and nanoparticle tracking analysis, and we will discuss their applicability and limitations. Finally, we discuss four methods that are not commercially available: Raman microspectroscopy, micro nuclear magnetic resonance, small‐angle X‐ray scattering (SAXS), and anomalous SAXS. These methods are currently being explored to study vesicles and are likely to offer novel information for future developments.